The penal sanction in the Colombian Peace Agreement with the FARC-EP and the international standard of proportionality of punishment (2018)
The article aims to solve whether the penalties prescribed in the Final Peace Agreement between the Government of Colombia and the FARC-EP to punish those responsible of international crimes are compatible with the international standard of proportionality of the sanction, based on an interpretation of the treaties and the jurisprudence of the International Criminal Law, the International Humanitarian Law and the Inter-American System of Human Rights.